Non-inferiority Trial Investigating the Efficacy of Non-steroidal Anti-inflammatory Drugs and Antimicrobial Treatment of Mild to Moderate Clinical Mastitis in Dairy Cows With Long-lasting Udder Diseases - Krömker, Volker; Schmenger, Anne; Klocke, Doris; Mansion-de Vries, Ellen Maria; Wente, Nicole; Zhang, Yanchao; Leimbach, Stefanie (Frontiers in Veterinary Science, 2021)
To reduce ineffective antimicrobial usage in the treatment of non-severe clinical mastitis (CM) in cows with long-lasting udder diseases, non-antibiotic therapy with a non-steroidal anti-inflammatory drug (NSAID) was conducted and evaluated in a non-blinded, positively controlled, non-inferiority trial. Therefore, systemic ketoprofen treatment for three times at intervals of 24 hours was evaluated in comparison with the reference treatment of solely antibiotic therapy in a field study on nine free-stall dairy farms located in Northern Germany. Cows with previous CM cases in current lactation and/or with long-lasting high somatic cell counts in preceding dairy herd improvement test days were randomly allocated to one of the two treatment groups in cases of mild to moderate CM. Quarter foremilk samples of the affected quarters were taken for cyto-bacteriological investigation before treatment as well as approximately 14 days and 21 days after termination of therapy. Both treatment groups were compared regarding the bacteriological cure (BC) as the primary outcome. Clinical cure (CC) and no CM relapse within 60 days after end of treatment (no R60) were chosen as secondary outcomes. The study resulted in the following outcomes: Streptococcus uberis was most frequently identified in microbiological culture from pre-treatment samples, followed by Staphylococcus aureus and Escherichia coli and other coliforms. No significant differences between the NSAID treatment and the reference treatment were detected regarding CC and CM recurrence (no R60). Although the sole ketoprofen therapy resulted in a numerically lower likelihood of BC, there were no significant differences to the reference treatment. Considering the selection criteria in this study, the results indicate that in mild to moderate CM cases exclusive treatment with ketoprofen may constitute an alternative to antimicrobial intramammary therapy, providing an opportunity for reduction of antibiotic usage.